ESTIMASI POPULASI MACAN DAHAN SUNDA (Neofelis diardi) DI SUAKA MARGASATWA BUKIT RIMBANG BUKIT BALING MENGGUNAKAN BANTUAN PERANGKAP KAMERA - Maryani '; Ahmad Muhammad; Sunarto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Since 2006, scientists consider Sundaland clouded leopards Neofelis diardi as a unique species, different from the mainland Asia species N. nebulosa. The species is categorized as vulnerable in the IUCN Red List and is only found in Borneo and Sumatra islands. Massive deforestation in Sumatra is believed to increase the endangerment of this species. This study aimed to estimate the density of this species and assess its conservation status in Central Sumatra, especially in Rimbang Baling Wildlife Reserve. In this study we present the density estimation which was calculated with spatial capture-recapture models using photographic data resulted from a tiger-focused camera-trapping study. This study used 40 cameras at 20 stations, with accumulation of 1.710 effective camera trap days, resulted 32 independent images of 8 individually identifiable of clouded leopards. They consisted of 5 males, 1 female and 2 could not be determined. The density of clouded leopard in this study was 2,80±1,11 (D±SE) individual/100 km2. This density is considered as relative lower than the estimates of Sundaland clouded leopard densities documented in some other areas in Borneo and Sumatra. This suggests that Rimbang Baling can be managed to support a healthy and perhaps viable population of Sundaland clouded leopards in Central Sumatra.